PEMBELAJARAN MINI BRIDGE BAGI SISWA SEKOLAH DASAR - Sugeng. SR (Jurnal Pendidikan Jasmani Indonesia, 2010)
Abstract This minibridge game is used for the basic understanding of the real bridge game; it includes the way for deciding the contract or the system of the game for the elementary school students who want to play the real bridge game. Mini bridge is used for the learning activity of the sport teacher in making the plan of the teaching and learning activity for the elementary school students and giving the teaching material about the true of deciding contract in the real bridge game, include the own cards and the own partner cards. It hopes that mini bridge game can help the sport teachers and the students, who have the difficulty in learning, understanding, mastering and the way to decide the true contract or the technique in the real bridge game. Keywords: Mini bridge game, Elementary schools.